2004
DOI: 10.1177/00222194040370050401
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Adjustment and School Functioning of Young Adolescents with Multiple Versus Single Learning Disabilities

Abstract: Early adolescents (Grades 6-8) with multiple learning disabilities (LD; reading and math) in inclusive settings were compared to adolescents with single LD (reading or math) and typically achieving (TA) peers regarding their psychosocial functioning in two areas of adolescent well-being: emotional adjustment and school functioning. The Behavior Assessment System for Children (Reynolds & Kamphaus, 1998) Self-Report of Personality for adolescents was used to determine well-being. One hundred twenty middle school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 50 publications
3
59
1
6
Order By: Relevance
“…It could be that LD gives some of the students the strength and decisiveness to work harder and to excel by developing empathy toward others, which may make them better advisors to their friends. These findings are in contrast to many other studies that found that LD children experienced more depression (see review by Sideridis, 2006), depression and a higher incidence of suicide (Bender, Rosenkrants, & Crane, 1999;Heath, & Ross, 2000;Huntington & Bender, 1993;Martinez & Semrud-Clikeman, 2004), and a poorer selfimage and self-esteem (Margalit & Zak 1984;Rowley, 1981;Rozenberg & Gaier, 1977;Smith, 1979;Yauman, 1980).…”
Section: Article In Presscontrasting
confidence: 90%
“…It could be that LD gives some of the students the strength and decisiveness to work harder and to excel by developing empathy toward others, which may make them better advisors to their friends. These findings are in contrast to many other studies that found that LD children experienced more depression (see review by Sideridis, 2006), depression and a higher incidence of suicide (Bender, Rosenkrants, & Crane, 1999;Heath, & Ross, 2000;Huntington & Bender, 1993;Martinez & Semrud-Clikeman, 2004), and a poorer selfimage and self-esteem (Margalit & Zak 1984;Rowley, 1981;Rozenberg & Gaier, 1977;Smith, 1979;Yauman, 1980).…”
Section: Article In Presscontrasting
confidence: 90%
“…The association with calculation disorders at junior secondary schools seems to be an additional risk factor for lower global self-esteem, experience or perception of a lower social support (by the classroom, parents and friends), higher attention defi cit, higher emotional and depression symptoms, and higher school maladjustment. [48,49] Reading diffi culties Maughan et al's [50] research was conducted on children with persistent reading diffi culties under the 6th percentile, children who were therefore very similar to those with a diagnosis of dyslexia. They also found that attention defi cit in comorbidity plays a signifi cant role in connecting the correlation with psychopathology, especially the externalizing one (e.g., delinquency).…”
Section: Dyslexiamentioning
confidence: 99%
“…The stigma associated with learning disorders, 36 particularly in school-aged children, might have influenced responses on the ImPACT, because it was administered in a group setting. 7,20,25,31 As learning difficulties have the potential to affect tests of cognitive ability, these results suggest that the method by which adolescents are asked to report their disabilities should be carefully considered. 6,26 From a clinical perspective, the importance of an accurate concussion history during neurocognitive testing can be debated.…”
mentioning
confidence: 99%